2017
DOI: 10.1080/22201181.2017.1332809
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of delirium in the intensive care unit

Abstract: Delirium poses a significant burden on our healthcare, with patients in the intensive care unit (ICU) at an increased risk for developing this disorder. In addition, the ICU environment poses unique challenges in the assessment of delirium. It is paramount that the healthcare provider has an understanding of delirium in ICU, and monitors for it vigilantly. There have been various scoring systems developed to assist in this regard. However, the most commonly used and validated tools for the assessment of deliri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
(148 reference statements)
0
5
0
2
Order By: Relevance
“…Although the aim of this SR is not to explore professionals’ decision making, diagnosis, and instruments used for the early detection of delirium, the results showed that this syndrome is often misdiagnosed [ 1 , 5 , 13 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the aim of this SR is not to explore professionals’ decision making, diagnosis, and instruments used for the early detection of delirium, the results showed that this syndrome is often misdiagnosed [ 1 , 5 , 13 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Timely diagnosis and management may curtail the duration and associated morbidity and mortality of delirium [ 36 ] or even reverse symptoms and give the critically ill individual a better quality of life, avoiding prolonged hospitalizations and/or other comorbidities [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of delirium varies widely from 16.1% to 83.3% in ICU patients, especially among those undergoing mechanical ventilation (60–80%) . The variable incidence is due to: different patient baseline characteristics; types of ICU (medical, surgical or both); illness severity; screening tools for diagnosis of delirium; and concomitant medications .…”
Section: Discussionmentioning
confidence: 99%
“…Bendras jautrumas 95-100 procentų; ventiliuojamiems pacientams jautrumas 92-100 procentų. Bendras specifiškumas 89-93 procentai, ventiliuojamiems pacientams 88-100 procentų [25].…”
Section: Tyrimo Rezultataiunclassified
“…Be to, ICDSC lengva įtraukti į kasdienę praktiką, nes įvertinimui naudojami duomenys, kurie ir taip stebimi IT skyriuose. Kitas ICDSC pliusas yra tas, jog galima įvertinti ir subsindrominį delyrą [25], be to, skalė yra jautresnė (99%), lyginant su CAM-ICU, nors specifiškumas (64%) yra ženkliai mažesnis. ICDSC, lyginant su CAM-ICU, geriau numato baigtis, tačiau CAM-ICU yra tinkamesnis ventiliuojamiems pacientams, patikimiau atmeta delyro diagnozę, jeigu jo nėra [30,31].…”
Section: Diskusija Ar Geriausiai Ištirtos Skalės -Geriausias Pasirinkimas?unclassified